A novel method for culturing stellate astrocytes reveals spatially distinct Ca2+ signaling and vesicle recycling in astrocytic processes - Wolfes, A; Ahmed, S; Awasthi, A; Stahlberg, M; Rajput, A; Magruder, D; Bonn, S; Dean, C (Rockefella University Press, 2016)
Interactions between astrocytes and neurons rely on the release and uptake of glial and neuronal molecules. But whether astrocytic vesicles exist and exocytose in a regulated or constitutive fashion is under debate. The majority of studies have relied on indirect methods or on astrocyte cultures that do not resemble stellate astrocytes found in vivo. Here, to investigate vesicle-associated proteins and exocytosis in stellate astrocytes specifically, we developed a simple, fast, and economical method for growing stellate astrocyte monocultures. This method is superior to other monocultures in terms of astrocyte morphology, mRNA expression profile, protein expression of cell maturity markers, and Ca(2+) fluctuations: In astrocytes transduced with GFAP promoter-driven Lck-GCaMP3, spontaneous Ca(2+) events in distinct domains (somata, branchlets, and microdomains) are similar to those in astrocytes co-cultured with other glia and neurons but unlike Ca(2+) events in astrocytes prepared using the McCarthy and de Vellis (MD) method and immunopanned (IP) astrocytes. We identify two distinct populations of constitutively recycling vesicles (harboring either VAMP2 or SYT7) specifically in branchlets of cultured stellate astrocytes. SYT7 is developmentally regulated in these astrocytes, and we observe significantly fewer synapses in wild-type mouse neurons grown on Syt7(-/-) astrocytes. SYT7 may thus be involved in trafficking or releasing synaptogenic factors. In summary, our novel method yields stellate astrocyte monocultures that can be used to study Ca(2+) signaling and vesicle recycling and dynamics in astrocytic processes.